A concise history of Spain - Phillips, William D. (Cambridge concise histories, 2016)
"The rich cultural and political life of Spain has emerged from its complex history, from the diversity of its peoples, and from continual contact with outside influences. This updated edition traces that history from prehistoric times to the present, focusing particularly on culture, society, politics, and personalities. Written in an engaging style, it introduces readers to key themes that have shaped Spain's history and culture. These include its varied landscapes and climates; the impact of waves of diverse human migrations; the importance of its location as a bridge between the Atlantic and the Mediterranean and Europe and Africa; and religion, particularly militant Catholic Christianity and its centuries of conflict with Islam and Protestantism, as well as debates over the place of the Church in modern Spain. Illustrations, maps, and a guide to further reading, major cultural figures, and places to see, make the history of this fascinating country come alive"--